The Attitude of Ukrainian Student Youth Towards Democracy in Ukraine - Kamionka, Mateusz; Каміонка, Матеуш; Камионка, Матеуш. (Східноєвропейський національний університет імені Лесі Українки, 2020)
The young generation is often overlooked in scientific discourse, although it is the youth (students) who often play a leading role in political and social change in the country. One such case is Ukraine, where it is the young people who started the largest protests in the country‟s thirty-year independent history. The presented article is an attempt to characterize the Ukrainian generation of «freedom» (Marzęcki, 2020) (youth people born during the period of Ukrainian independence, that are not impact of authoritarian regime socialization) from a socio-political perspective. The main research goal of this article is an endeavour to fully understand, describe and explain the attitude of the young generation (students) towards democracy (the article also includes comparisons to polish youth). This specific objective was achieved by analysing survey data. On the other hand, specific issues and problems identified at the quantitative research stage were examined based on data collected during in-depth interviews with sixteen students in Ukraine. In this sense, a second important specific goal has been achieved, i.e. diagnosis, description and explanation of behavioural patterns (political activity) dominating the social consciousness of students, which are considered justified and effective in relation to the world of politics. Author himself, conducted qualitative (IDI – 16 respondents) and quantitative research (1043 surveys) on a representative group of youth respondents in Ukraine. Quantitative research has been conducted in fourteen universities, preserving the territorial diversification. The results contained in the summary of the article, however, are not very optimistic. It is safe to say that the democratic system is in crisis, and the revolutionary cycle is still probably not completed in Ukraine.

У статті схарактеризовано українське покоління «свободи», до якого, за визначенням автора, належать молоді люди, котрі народилися за часів незалежності України й на котрих не впливала соціалізація авторитарного режиму, із соціально-політичного погляду. Основна мета цієї статті – спроба повністю зрозуміти, описати та пояснити ставлення молодого покоління (студентів) до демократії. Мету досягнуто шляхом аналізу даних опитування. З іншого боку, конкретні теми та проблеми визначено на етапі кількісного дослідження й вивчено на основі даних, зібраних під час детальних інтерв‟ю зі студентами в Україні. На цьому етапі досягнуто другу важливу мету – це діагностика, опис та пояснення біхевіоральних (поведінкових) моделей суспільно-політичної ді-яльності, що домінують у суспільній свідомості студентів і вважаються виправданими й ефективними щодо світу політики. Проведено якісні (метод IDI) та кількісні (1043 опитування) дослідження репрезентативної гру-пи респондентів студентської молоді в Україні.

В статье анализируется украинское поколение «свободы» с социально-политической точки зрения, определения его как поколения молодых людей, которые родились во времена независимости Украины и социализиро-вались вне влияния авторитарного режима. Основная цель исследования – попытка полностью понять, описать и объяснить отношение молодого поколения (студентов) к демократии. Цель достигнута путем анализа данных опроса, а именно: проводились качественные (метод IDI) и количественные (1043 опрос) исследования репре-зентативной группы молодежи в Украине. Конкретные проблемы, определенные на этапе количественного исследования, изучались на основе данных, собранных во время детальных интервью со студентами в Ук-раине. На этом этапе достигалась вторая важная цель – диагностика, описание и объяснение бихевиоральных моделей общественно-политической деятельности, которые доминируют в общественном сознании студентов и считаются оправданными и эффективными в мире политики.
Ставлення української студентської молоді до демократії в Україні
Отношение украинской студенческой молодежи к демократии в Украине
Keywords: democracy; youth; students; Ukraine; protests; socio-logical surveys; демократія; молодь; студенти; Україна; протести; соціологічні опитування; 323.2(477)